Factors directing individuals to computer games in the process of evaluating recreational activities - Yıldız Kadir; Güzel Pınar; Esentaş Melike (Sciendo, 2020)
This study aims to examine the motivational factors that direct individuals to computer games in the process of evaluating leisure activities. The study is designed in descriptive and relational survey models, which are among the quantitative research patterns. A total of 1677 individuals participated in the study. A personal information form and the Computer Gaming Motivation Scale were used. An independent sample t-test, one-way analysis of variance, and Pearson correlation test were used to analyze the data. According to the results, there were significant differences in the concentration, entertainment, escape, learning, and socialization sub-dimensions of the participants in favor of the groups playing in Internet cafes. The findings indicate that when more time is spent with information and communication technologies, there is a decrease in concentration and an increase in entertainment and escape. Furthermore, when the relationship between the sub-dimensions of the scale was examined, positively moderate and high correlations were found among concentration, entertainment, escape, learning, and socialization. As a result, rapid technological changes and developments provide many opportunities for individuals. It is thought that individuals' busy work lives and monotonous daily routines cause them to prefer easily accessible activities during their leisure time.